To profit or not to profit; the commercial transformation of the nonprofit sector (Cambridge : Cambridge University Press, 2000)
This book is about: Basic issues and perspective; Industry studies; Overview, conclusions, and public-policy issues; ...
Keywords: Finance; Management; Organization; Nonprofit organizations -- Management; Nonprofit organizations -- Finance